(untitled) (Research, Society and Development, 2023)
The aim of the present study was to demonstrate the importance of diagnosing endo- periodontal lesions.This patology includes periodontal tissue end endodontics tissue, commitee. Thea knowledge of inter-relation between endodontics and periodontics is fundamental to trat this illness. For that, an electronic search was carried out through the PUBMED and ACADEMIC GOOGLE database involving the years between 2017 and 2022. The descriptors used for the literary search involved combinations with the following words: endodontics, periodontal disease endo-periodontal injuries.Only articles that were presented with full text were included in this study, therefore, those that only contained the abstract were discarded. Articles that were in languages other than Portuguese or English were also not used. Literature is clear when it claims to know deeper into biology of the periodontum and endodontum well as destabilizing factores of this biology.